2021
DOI: 10.3389/fimmu.2021.768820
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Irradiated Fowl Cholera Mucosal Vaccine: Potential Vaccine Candidate for Safe and Effective Immunization of Chicken Against Fowl Cholera

Abstract: Fowl cholera (FC) caused by Pasteurella multocida is among the serious infectious diseases of poultry. Currently, formalin inactivated FC (FI-FC) vaccine is widely used in Ethiopia. However, reports of the disease complaint remain higher despite the use of the vaccine. The aim of this study was to develop and evaluate gamma-irradiated mucosal FC vaccines that can be used nationally. In a vaccination-challenge experiment, the performance of gamma-irradiated P. multocida (at 1 kGy) formulated with Montanide gel/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Cross-linked polyacrylic polymers (Carbopol) can enhance the time of mucosal surface adhesion antigen and induce systemic antigen-specific IgG responses after intranasal vaccination ( Coucke et al, 2009 ). MONTANIDE™ Gel 01 (SEPPIC, France) is based on the stable gel polymers of sodium polyacrylate in water, and it prolongs the residence time of the vaccine in the nasal mucosa ( Deville et al, 2012 ; Li et al, 2019 ; Dessalegn et al, 2021 ). Pattern recognition receptor agonists have been extensively studied as mucosal adjuvants and can bind to pathogen recognition receptors on dendritic cells to activate downstream immune signals ( Velasquez et al, 2010 ; Hjelm et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-linked polyacrylic polymers (Carbopol) can enhance the time of mucosal surface adhesion antigen and induce systemic antigen-specific IgG responses after intranasal vaccination ( Coucke et al, 2009 ). MONTANIDE™ Gel 01 (SEPPIC, France) is based on the stable gel polymers of sodium polyacrylate in water, and it prolongs the residence time of the vaccine in the nasal mucosa ( Deville et al, 2012 ; Li et al, 2019 ; Dessalegn et al, 2021 ). Pattern recognition receptor agonists have been extensively studied as mucosal adjuvants and can bind to pathogen recognition receptors on dendritic cells to activate downstream immune signals ( Velasquez et al, 2010 ; Hjelm et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…MONTANIDE TM Gel 01 (SEPPIC, France) is a mucoadhesive polymeric adjuvant that can improve the safety and efficacy of mucosal vaccination (Deville et al, 2012;Li et al, 2019;Dessalegn et al, 2021). Gel 01 is based on a dispersion of highly stable gel particles of sodium polyacrylate in 10.3389/fmicb.2022.976220 water.…”
Section: Introductionmentioning
confidence: 99%
“…Immune responses and the protection in a mouse model were evaluated and found that both live attenuated vaccines (71%) and inactivated vaccines (51%) could not provide complete protection against homologous serotypes and did not protect against heterologous serotypes [ 11 ]. To address the above research questions, researchers have evaluated new types of vaccine such as subunit vaccines and DNA vaccines [ 12 15 ]. However, the correct folding, post-translational modification of proteins and harsh storage conditions still limit the development of related vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, for making the H9N2 IWV vaccine, H9N2 AIV is generally inactivated with formalin or β-propiolactone, which are poor in cellular and mucosal immune responses. However, recently a gamma-irradiated inactivated vaccine against fowl cholera enhances strong mucosal immunity after intranasal vaccination in chickens (Dessalegn et al 2021). This strategy may be also practical in the H9N2 IWV vaccine.…”
Section: Inactivated Vaccinementioning
confidence: 99%